Effects of dual-task training in patients with post-stroke cognitive impairment: A randomized controlled trial - Sun, Ruifeng; Li, Xiaoling; Zhu, Ziman; Li, Tiancong; Zhao, Man; Mo, Linhong; Li, Wenshan; Xi, Xiaoshuang; Huang, Peiling; Gong, Weijun (Frontiers in Neurology, 2022)
Background: Evidence for the efficacy of cognitive–motor dual task training (CMDT) in patients with post-stroke cognitive impairment (PSCI) and no dementia is still lacking. Methods: A randomized, single-blind active control design was implemented using adaptive CMDT for 40 minutes a day, 5 days a week, for 4 weeks. Assessments included global cognitive function (primary outcomes) and regional brain functional activity (secondary outcomes). Results: Thirty-three patients were randomized across Beijing Rehabilitation Hospital Capital Medical University in Beijing. At the end of the intervention, the CMDT group showed significant improvement in the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) relative to the cognitive training (CT) group. The results of event-related potential and functional near-infrared spectroscopy showed that CMDT can shorten the reaction time of central neurons and significantly accelerate the nerve conduction velocity (P＜0.05). Conclusion: CMDT in patients with PSCI improved global cognitive function, which was supported by the improved neural efficiency of associated brain areas.